Clearing the undergrowth: detection and quantification of low level impurities using 19F NMR. Issue 1 (1st December 2016) - Moutzouri, Pinelopi; Kiraly, Peter; Phillips, Andrew R.; Coombes, Steven R.; Nilsson, Mathias; Morris, Gareth A.
Abstract : A new 19 F NMR method, ODYSSEUS, allows low level impurities to be detected without interference from 13 C satellites. Abstract : A new method for the analysis of low level impurities in sparsely fluorinated species allows measurement of clean high dynamic range 19 F spectra, fully decoupled and free of interfering signals from 13 C isotopomers.